1993
DOI: 10.1073/pnas.90.24.11728
|View full text |Cite
|
Sign up to set email alerts
|

Mevalonate availability and cardiovascular functions.

Abstract: Data delineating the relationship between disorders of cholesterol metabolism and elevated blood pressure (BP) do not exist. We postulated that mevalonate, the metabolic precursor of endogenous cholesterol and the direct product of 3-hydroxy-3-methylglutaryl-CoA reductase, was a contributing factor for the maintenance of vascular tone and systemic BP. We conducted in vivo, ex vivo, and in vitro experiments in normotensive and hypertensive rats, where exogenous mevalonate and lovastatin, a competitive inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1994
1994
1997
1997

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…A similar impact of lovastatin was observed previously by us in vivo and in vitro (9). Our experiments cannot clearly separate the effect of lovastatin on the endothelium from that on the smooth muscle since the response to SNP was also impaired.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…A similar impact of lovastatin was observed previously by us in vivo and in vitro (9). Our experiments cannot clearly separate the effect of lovastatin on the endothelium from that on the smooth muscle since the response to SNP was also impaired.…”
Section: Discussionsupporting
confidence: 64%
“…In our earlier study (9), lovastatin appeared to act on several pathways including NE-induced contraction and acetylcholine and sodium nitroprusside (SNP)-induced relaxation. It is known that stimulation of membrane receptors, such as the adrenergic and muscarinic receptors, triggers the elevation of 1.…”
Section: Introductionmentioning
confidence: 99%
“…In two recent studies (6, 7), we observed that systemic blood pressure and vascular tone were dependent on the metabolic availability of mevalonate, an early precursor of cholesterol. Reduction of mevalonate availability with lovastatin, a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) 1 reductase inhibitor, enhanced the response of conductance and resistance vessels to vasoconstrictors, impaired vasodilation, and raised arterial pressure (6). Increased mevalonate availability with exogenous mevalonate had opposite effects and normalized the reactivity of vessels exposed to lovastatin in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…However, a direct effect on PKC is unlikely as farnesol does not affect PKC cellular localization in cell lines derived from normal tissue (12). Other studies have reported the existence of a farnesol-specific, orphan nuclear receptor in vertebrate cells, the farnesoid X-activated receptor, but the role of this receptor in cell signaling pathways still needs to be defined (13,14).We have shown that mevalonate (MVA) availability is an important determinant of vascular tone in animal and human arteries (15,16). Decreased vascular MVA availability following treatment with lovastatin, a 3-hydroxy-3-methylglutarylCoA reductase inhibitor, was associated with an increase in the response to vasoconstrictors, whereas addition of MVA to the arteries inhibited vasoconstriction.…”
mentioning
confidence: 99%
“…We have shown that mevalonate (MVA) availability is an important determinant of vascular tone in animal and human arteries (15,16). Decreased vascular MVA availability following treatment with lovastatin, a 3-hydroxy-3-methylglutarylCoA reductase inhibitor, was associated with an increase in the response to vasoconstrictors, whereas addition of MVA to the arteries inhibited vasoconstriction.…”
mentioning
confidence: 99%